2022
DOI: 10.51821/85.3.10211
|View full text |Cite
|
Sign up to set email alerts
|

Liver abscesses in the Western pediatric population

Abstract: Background and study aims: Liver abscesses are rare in the Western pediatric population and data on predisposing factors and etiology are scarce. We aimed to describe predisposing factors, microbiological characteristics, and treatment. Patients and methods: Retrospective analysis of children admitted to two tertiary care hospitals in Belgium from 1 January 1996 to 31 December 2019. We analyzed clinical features, predisposing factors, imaging characteristics, microbiological data, treatment, and outcome in ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The low sensitivity of blood culture is also indicated in previous reports. 1,4 Although severe LAs are known to be associated with chronic granulomatous disease, 5 this patient showed no signs of inborn errors of immunity.…”
Section: Respiratory Symptoms Are the First Presentation Of Liver Abs...mentioning
confidence: 66%
“…The low sensitivity of blood culture is also indicated in previous reports. 1,4 Although severe LAs are known to be associated with chronic granulomatous disease, 5 this patient showed no signs of inborn errors of immunity.…”
Section: Respiratory Symptoms Are the First Presentation Of Liver Abs...mentioning
confidence: 66%
“…However, to ensure safe and effective drainage, some degree of wall maturation is awaited in most cases, although the timing of sufficient maturation is still controversial. In their retrospective series, Choudhury et al demonstrated full encapsulation in 56% of cases at 4 weeks, validating the suggestion to wait 4 weeks if possible and to guide the decision to drain by imaging results (12).In the current edition Grossar et al report on the diagnosis and favorable outcome of liver abscesses in children and highlight the need to obtain invasive cultures as soon as possible (13).…”
mentioning
confidence: 88%